Xylem vessel morphology of pigeon pea (Cajanus cajan) under drip and surface irrigation using scanning electron microscopy - Jeyajothi , R; Vinothini , N; Vasanth P, P; Marimuthu , S; Akshaya , SB (Plant Science Today, 2025)
The study aimed to analyze the morphological attributes of the root and stem xylem diameter of pigeon pea through scanning electron microscopy to understand its structural and functional characteristics under varying conditions and provide significant insights into the structural variations caused by different irrigation methods.​ Through Scanning electron microscope imaging, distinct differences in vessel architecture, such as size and wall thickness, were observed in root and stem, which may impact water and nutrient transportation efficiency and overall plant health. These variations are vital for understanding how irrigation strategies affect the physiological function and adaptation of pigeon pea, providing crucial information for improving agricultural practices and enhancing crop yield in varying environmental conditions. The results emphasize the importance of optimizing irrigation methods to promote better vascular development in crops, ultimately leading to sustainable agricultural practices. Scanning electron microscopy images revealed distinct differences in xylem vessel structure between drip and surface irrigation of pigeon peas.